Afla necunscuta E :
( 6 x e -5) : 7 =7
Răspunsuri la întrebare
Răspuns de
1
6*e-5= 7*7
6*e-5=49
6*e=49+5
6*e=54
e=54/6
e=9
6*e-5=49
6*e=49+5
6*e=54
e=54/6
e=9
Bibu1234:
mersii
Răspuns de
1
(6*e-5):7=7
6*e-5=7*7
6*e-5=49
6*e=49+5
6*e=54
e=54:6
e=9
proba:(6*9-5):7=(54-5):7=49:7=7
6*e-5=7*7
6*e-5=49
6*e=49+5
6*e=54
e=54:6
e=9
proba:(6*9-5):7=(54-5):7=49:7=7
Alte întrebări interesante
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Fizică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă